Potential of house yard plants as an alternative for dengue vector control in the tsunami area settlement of Banda Aceh City - Elita Agustina,, Amin Setyo Leksono, Zulfaidah Penata Gama, Bagyo Yanuwiadi, Mauliza Sukma (Journal of Applied Pharmaceutical Science, 2022)
The rebuilding of settlements after the 2004 Aceh tsunami has created a new home environment. Human activities and behavior in managing new home environments have inadvertently contributed to creating new habitats for Aedes. One of the factors that support and limit the presence of Aedes is the plants around the house. Plants also influence mosquitoes in a place; they are known as mosquito-attracting plants and mosquito-repellent plants. This study aimed to determine the potential of house yard plants as an alternative to dengue hemorrhagic fever vector control in the tsunami settlement area of Banda Aceh City. This research is an explorative survey using 200 house yards in the tsunami area settlement of Banda Aceh City. The result of the study found two species of Aedes (Aedes aegypti and Aedes albopictus) and 63 families of house yard plants with 150 species in the tsunami area settlement of Banda Aceh City. Totally, 63 families have the potential as dengue vector repellents and 17 as dengue vector attractants. Plants in the tsunami settlements of Banda Aceh City have the potential as an alternative for controlling dengue vectors.
Keywords: Aedes, attractant, dengue vector control, house yard plants, potential repellent